Life-Cycle Cost Assessment of Real Estate Assets: Ukrainian Realities and International Experience, Challenges and Prospects - POPOVYCHENKO, Iryna (Ways to Improve Construction Efficiency, 2025)
This article explores the theoretical foundations and practical aspects of applying the concepts of Life-Cycle Costing (LCC) and Whole-Life Costing (WLC) to assess the economic efficiency of investments in the construction and operation of real estate assets. In the context of economic instability, inflationary pressures, energy crises, and the growing need for resource efficiency, the relevance of approaches that account not only for construction phase expenditures but also for costs incurred throughout the entire life cycle of an asset is significantly increasing. The study examines the features of the national regulatory approach, with a focus on the provisions of the Ukrainian standard DSTU ISO 15686-5:2020, which establishes methodological foundations for LCC assessment. The key barriers to the implementation of LCC and WLC methods in Ukraine are identified as insufficient regulatory support, low awareness among market participants, a lack of standardized tools for economic calculations, and an underdeveloped culture of long-term financial planning in the construction sector. A comparative analysis of the LCC and WLC concepts is presented. LCC is primarily focused on expenditures associated with design, construction, operation, maintenance, and disposal, while WLC also accounts for externalities, social and environmental factors, including asset residual value and environmental impact costs. This distinction is particularly relevant in the context of the EU’s sustainable construction priorities and Ukraine’s post-war reconstruction. The article discusses international experience in integrating LCC/WLC approaches into project management practices as a positive reference point for the Ukrainian construction industry. The feasibility of implementing life-cycle assessment mechanisms in the planning of public and private construction projects is substantiated, with the aim of improving investment efficiency, reducing energy consumption, increasing procurement transparency, and establishing an effective value management system throughout an asset’s service life. The paper also outlines future research directions, including the digitalization of LCC/WLC calculations (particularly integration with BIM technologies), the development of national industry-specific databases on maintenance and repair costs, and the advancement of tools for comparative analysis of project alternatives based on life-cycle principles. It is emphasized that the implementation of LCC and WLC concepts has the potential not only to reduce costs but also to achieve broader socio-economic and environmental goals in real estate management. The need to integrate social and behavioral dimensions into life-cycle assessment (LCA) methodologies for construction assets is also underlined.